2014
DOI: 10.1111/cdep.12067
|View full text |Cite
|
Sign up to set email alerts
|

A Social–Ecological, Process‐Oriented Perspective on Political Violence and Child Development

Abstract: Youths’ risk for adjustment problems in contexts of political violence is well-documented. However, outcomes vary widely, with many children functioning well. Accordingly, moving beyond further documenting the risk for many negative outcomes associated with living in contexts of political violence, a second generation of research is moving towards identifying the mechanisms and conditions that contribute to children’s adjustment. Increasing support is emerging for understanding effects on children in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 49 publications
4
51
0
Order By: Relevance
“…Moreover, this political socialization, despite its lack of uniformity, has a lasting impact on the lives of society members in their adulthood, and thus plays a major role in the dynamics of the intractable conflict due to the powerful nature of this context (Bar-Tal, Diamond, & Nasie, 2015;Cummings et al, 2014). Accordingly, this article examines political socialization in the specific Israeli context of intractable conflict, among Israeli-Jewish young children, providing a number of insights, implications, and consequences.…”
Section: Political Socialization In An Intractable Conflictmentioning
confidence: 99%
“…Moreover, this political socialization, despite its lack of uniformity, has a lasting impact on the lives of society members in their adulthood, and thus plays a major role in the dynamics of the intractable conflict due to the powerful nature of this context (Bar-Tal, Diamond, & Nasie, 2015;Cummings et al, 2014). Accordingly, this article examines political socialization in the specific Israeli context of intractable conflict, among Israeli-Jewish young children, providing a number of insights, implications, and consequences.…”
Section: Political Socialization In An Intractable Conflictmentioning
confidence: 99%
“…reflect the need for understanding adjustment trajectories from a developmental perspective, including process-oriented tests of treatment effectiveness models (Cummings, Goeke-Morey, Merrilees, Taylor, & Shirlow, 2014;Cummings & Valentino, 2015).…”
mentioning
confidence: 99%
“…For example, emotional insecurity about the family (Cummings et al, 2012) or community have repeatedly been identified as mediating the effects of experience with SAB on child and adolescent adjustment (Cummings et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…That is, the conceptualization adopted in most research is that contexts of political violence, for example, experience with such violence results in elevated adjustment problems in children. Moreover, the great majority of research studies in this area are cross-sectional (for discussion, see Cummings et al, 2014), so that the direction of interrelations between exposure to political violence and child adjustment problems cannot be determined. Thus, in the absence of longitudinal research, three possibilities for the directions of effect between political violence and child adjustment remain: (a) exposure to political violence is causally related to child Bidirectional Relations, Political Violence and Adolescent Adjustment 4 adjustment problems, (b) child adjustment problems are causally related to exposure to political violence, and (c) the direction of causal effects flows both ways.…”
Section: Adolescent Adjustment Over Time In Northern Irelandmentioning
confidence: 99%